Shutting off the fuel supply to target metabolic vulnerabilities in multiple myeloma - Rana, Priyanka S.; Goparaju, Krishna; Driscoll, James J. (Frontiers in Oncology, 2023)
The deregulation of pathways that govern cellular bioenergetics represents a cancer hallmark. A common feature of cancer cells is the capacity to reprogram numerous key pathways that govern nutrient acquisition, anabolism and catabolism to enhance tumor growth and survival. Moreover, tumor initiation has been shown to require the autonomous reprogramming of pathways that control metabolic flux to meet the increased bioenergetic demands of transformed, cancerous cells. Tumors acquire the ability to obtain or produce needed metabolites from a nutrient-poor environment to maintain viability and enhance biomass. Alterations in intracellular and extracellular pathways that accompany cancer-associated metabolic reprogramming have profound intrinsic effects on gene expression, cellular differentiation, as well as extrinsic effects on the tumor microenvironment. Despite the vast amount of genetic and histologic heterogeneity seen within and between cancer types, a finite set of deregulated pathways have been identified that support core anabolic, catabolic, and redox balance activities. The incurable plasma cell dyscrasia multiple myeloma (MM) is characterized by tumor intrinsic alterations in glycolytic, fatty acid and glutamine metabolism and further altered by the hypoxic bone to augment tumor growth and drug resistance. Here, we discuss newly emerging tumor intrinsic and extrinsic metabolic mechanisms that support myelomagenesis, therapeutic resistance, and anti-tumor immunity. A nuanced evaluation of cancer and immune metabolism may reveal unforeseen vulnerabilities and therapeutic windows that can be exploited for the rational design of drug cocktails that improve patient outcomes.